ANALYSIS OF IMPROVING STUDENTS' LANGUAGE SKILLS THROUGH LITERACY ACTIVITIES IN CLASS 1 OF SDN 1 KOTAFAJAR - Oktanalisa, Cut; Sari, Siti Mayang; Binti Norhazaruddin, Nurul Fatehah (SENSEI RESEARCH CENTER, 2024)
Education, as an important thing in forming character and developing individual potential, is important in community development. At the basic education level, such as at SD Negeri 1 Kotafajar, educational institutions face various challenges and dynamics that can have a big impact on students' language abilities. Therefore, this research aims to conduct an in-depth analysis regarding improving students' language skills through literacy activities in Class 1. SD Negeri 1 Kotafajar, as an integral part of the education system, is expected to be able to provide a solid foundation in developing children's language skills while contributing on improving the overall quality of education. This research uses a qualitative approach with descriptive research type. Based on the interview results, it shows that literacy activities in Class 1 of SD Negeri 1 Kotafajar are integrated into the curriculum with a focus on reading, writing and speaking. Teachers have successfully integrated literacy into the curriculum with interactive methods, while parental support and teacher differentiation approaches have strengthened the effectiveness of this program. There has been a significant increase in students' interest in literacy, which is reflected in active participation in various reading and writing activities.